Living with hearing loss: exploring the lived experience of identity construction among adolescents and young adults - Sekoto, Lieketseng (Division of Public Health, 2023)
Background: Identity construction is the predominant developmental task in adolescence and young adulthood. Disabling hearing loss (HL) exacerbates the psychosocial challenges faced by adolescents and young adults (AYA) in their identity construction. The primary goal of this research study was to describe how AYA with disabling HL feel about and perceive their identity. Further, to understand the aspects underlying identity construction, with a focus on self-perception, navigating disability, social roles and relations, and community assimilation. Methodology: A qualitative interpretive phenomenological approach was adopted. Participants were a purposive sample of 5 Deaf and Hard-of-hearing AYA, aged 15 to 19 years. All participants were enrolled in schools for the deaf in the Western Cape and partook in semi-structured phenomenological conversations, where they narrated detailed accounts of their lived experiences with identity construction. Results: Interpretive phenomenological analysis was used to formulate themes. The superordinate themes of creating a self-concept, belonging, stress and being deaf emerged from participants' narratives. Identity construction occurs concurrently at several levels. At the personal level, deaf AYA create self-conceived ideals of who they are (Creating a self-concept), at relational level identity is nurtured through person-to-person and person-to-group interactions (Belonging). At societal level deaf AYA ascertain their position as individuals within the larger society (Being deaf). Protective factors, enabling factors and barriers that threaten positive identity construction, audiological health, and the psychosocial wellbeing of deaf AYA were identified. Overall, findings from this study indicate that the experience of identity construction for AYA with HL is layered and laden with challenges. Identity formation, albeit portrayed as a process of differentiation, is a balancing act. Identity is self-defined and equally exists in a collective identity with others. Identity construction also subjected participants to stress arising from the emotional burdens of HL, stigmatisation, and resultant psychological effects. Amid unique challenges, deaf AYA consciously developed coping mechanisms, some constructive and others detrimental to their audiological health, all while negotiating their position in the larger society. Conclusion: Study findings appeal to individuals in the caring professions such as audiologists, teachers, educational psychologists, and social workers to understand the nuances of identity construction for the successful transitional care of deaf adolescents moving into adulthood. Counselling needs to be responsive to the needs of deaf AYA, identity domains should be upheld in the provision of person-centered care and possible trajectories for identity crisis should be evaluated when considering school placement. Benefits of group counselling and peer support groups should be explored. There is a need for interventions that curb negative audiological health behaviours through assertiveness training and self-advocacy. The micro implementation of employment equity policies and legislation is critical to ensure the realisation of AYA's prospective identities in the South African workforce. Findings call for the reorientation of audiological rehabilitation and strengthening of interdisciplinary collaboration to meet the psychosocial needs of AYA with disabling HL.